Analisis perspektif masyarakat dalam memilih layanan kesehatan - Kumara, Denis; Christina, Tri Yahya; Setiani, Ditya Yankusuma; Kurniawan, Hendra Dwi (Holistik Jurnal Kesehatan, 2026)
Background: The increasing public need for and awareness of health poses a significant challenge for healthcare services to improve themselves in providing the best possible service to meet their needs. Therefore, it is important to explore the public's perspective in making decisions about choosing healthcare services based on healthcare service dimensions and marketing mix indicators. Purpose: To identify and analyze factors influencing public decisions in choosing healthcare services. Method: This qualitative descriptive study was conducted in five sub-districts in Surakarta, Central Java. Thirteen participants who met the inclusion criteria were recruited and selected using a stratified random sampling technique. A semi-structured interview guide was used to elicit themes. Interviews lasted 30-60 minutes and were audiotaped. The recordings were transcribed verbatim and then subjected to inductive content analysis following the Elo & Kyngas method. In-depth participant validation and data presentation were conducted to ensure data validity. Results: Thirteen key themes were identified that reflect the public's perspective on healthcare decisions. These include facilities, doctor schedule information and pricing via social media, punctuality, cleanliness, physical appearance, medical staff attitude and responsiveness, clarity of medical information, hospital comfort, personal experience, hospital reviews and accreditation, cost and health insurance, priority of distance, and ease of access and service flow. Conclusion: Public healthcare choices are influenced by hospital quality assessments, which include tangible evidence, reliability, responsiveness, assurance, and empathy. They are also supported by the 7Ps of the marketing mix, including product, price, place, promotion, people, process, and physical evidence, which collectively shape patient perceptions and decisions. Suggestion: Healthcare providers need to improve shared services by optimizing facilities, improving hygiene and safety standards, streamlining waiting times, streamlining processes, and improving healthcare provider communication to ensure more effective and patient-focused services.   Keywords: Community; Healthcare Services; Perspective.   Pendahuluan: Meningkatnya kebutuhan dan kesadaran masyarakat akan kesehatan, menjadi tantangan besar bagi layanan kesehatan untuk memperbaiki diri dalam memberikan layanan terbaik untuk masyarakat sesuai kebutuhan. Oleh karena itu, penting menggali perspektif masyarakat dalam mengambil keputusan untuk memilih layanan kesehatan berdasarkan dimensi layanan kesehatan dan indikator bauran pemasaran. Tujuan: Untuk mengidentifikasi dan menganalisis faktor-faktor yang memengaruhi keputusan masyarakat dalam memilih layanan kesehatan. Metode: Penelitian kualitatif deskriptif yang telah dilakukan di 5 kecamatan di Surakarta, Jawa Tengah. Sebanyak 13 partisipan yang memenuhi kriteria inklusi dilibatkan dan di pilih melalui teknik stratified random sampling. Pedoman wawancara semi-terstruktur digunakan untuk memperoleh tema. Wawancara dilakkan selama 30-60 menit dan di rekam. Hasil rekaman dilakukan verbatim dan dituangkan dalam sebuah transkrip, kemudian dianalisis isi induktif mengikuti metode Elo & Kyngas. Validasi partisipan dan penyajian data secara mendalam telah dilakukan untuk menjaga validitas data. Hasil: Didapatkan 13 tema utama yang mencerminkan perspektif masyarakat dalam mengambil keputusan untuk memilih layanan kesehatan, meliputi fasilitas, informasi jadwal dokter dan harga melalui media sosial, ketepatan waktu, kebersihan, tampilan fisik, sikap dan respon tenaga medis, kejelasan informasi medis, kenyamanan rumah sakit, pengalaman pribadi, ulasan dan akreditasi rumah sakit, biaya dan jaminan kesehatan, prioritas jarak, serta kemudahan akses dan alur pelayanan. Simpulan: Pemilihan layanan kesehatan oleh masyarakat dipengaruhi oleh penilaian kualitas rumah sakit yang mencakup tangibles, reliability, responsiveness, assurance, dan empathy, serta didukung oleh bauran pemasaran 7P seperti product, price, place, promotion, people, process, dan physical evidence, yang secara bersama membentuk persepsi dan keputusan pasien. Saran: Layanan kesehatan perlu meningkatkan mutu pelayanan melalui optimalisasi fasilitas, standar kebersihan dan keselamatan, efisiensi waktu tunggu, penyederhanaan alur, serta peningkatan komunikasi tenaga medis agar pelayanan lebih efektif dan berorientasi pada pasien.   Kata Kunci: Layanan Kesehatan; Masyarakat; Perspektif.